2020
DOI: 10.34257/gjreavol20is1pg17
|View full text |Cite
|
Sign up to set email alerts
|

The Load Distribution with Modification and Misalignment and Thermal Elastohydrodynamic Lubrication Simulation of Helical Gears

Abstract: A non-uniform model of the load per unit of length distribution of helical gear with modification and misalignment was proposed based on the meshing stiffness, transmission error, and load-balanced equation. The distribution of unit-lineload, transmission error (TE), and contact press of any point on the contact plane were calculated by the numerical method. The feature coordinate system was put forward to implement the helical preliminary design and strength ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Based on the meshing and lubrication theories, Peng et al (2018) introduced a non-Newtonian TEHL model for the helical gears with the modification and misalignment, and found that the double-crowning profile can improve the lubrication performance. Furthermore, Xue et al (2020) also numerically investigated effects of the modification and misalignment on the TEHL behavior of the helical gear. Recently, Xiao et al (2021) purposed a transient non-Newtonian TEHL point contact model for the modified herringbone gear drive, in which the fundamental parameters are obtained for the meshing and kinematics analyses, and studied the lubrication behavior of the gear pair in the steady running and start-stop phases.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the meshing and lubrication theories, Peng et al (2018) introduced a non-Newtonian TEHL model for the helical gears with the modification and misalignment, and found that the double-crowning profile can improve the lubrication performance. Furthermore, Xue et al (2020) also numerically investigated effects of the modification and misalignment on the TEHL behavior of the helical gear. Recently, Xiao et al (2021) purposed a transient non-Newtonian TEHL point contact model for the modified herringbone gear drive, in which the fundamental parameters are obtained for the meshing and kinematics analyses, and studied the lubrication behavior of the gear pair in the steady running and start-stop phases.…”
Section: Introductionmentioning
confidence: 99%